2020
DOI: 10.1042/bsr20194433
|View full text |Cite
|
Sign up to set email alerts
|

Plasma microRNA expression levels in HIV-1-positive patients receiving antiretroviral therapy

Abstract: MicroRNAs (miRNAs/miRs) may serve as therapeutic agents or targets in diseases in which the expression of proteins plays an important role. The aim of the present study was to compare the expression levels of specific miRNAs, as well as their correlation with markers of response to antiretroviral (ARV) therapy, in patients with human immunodeficiency virus type 1 (HIV-1) infection with and without resistance to highly active antiretroviral therapy (HAART). Methods: miRNA assays were performed on plasma samples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 35 publications
(60 reference statements)
0
15
0
Order By: Relevance
“…Additionally, miR-126-3p was found to be downregulated in HIV-1-positive patients receiving HAART. Interestingly, miR-126-3p was upregulated in patients with HAART resistance in comparison to patients without resistance [ 144 ••]. It was indicated that this is suggestive of miR-126 being linked with HIV treatment failure [ 144 ••].…”
Section: Micrornas In Angiotensin-converting Enzyme 2 Receptorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, miR-126-3p was found to be downregulated in HIV-1-positive patients receiving HAART. Interestingly, miR-126-3p was upregulated in patients with HAART resistance in comparison to patients without resistance [ 144 ••]. It was indicated that this is suggestive of miR-126 being linked with HIV treatment failure [ 144 ••].…”
Section: Micrornas In Angiotensin-converting Enzyme 2 Receptorsmentioning
confidence: 99%
“…Interestingly, miR-126-3p was upregulated in patients with HAART resistance in comparison to patients without resistance [ 144 ••]. It was indicated that this is suggestive of miR-126 being linked with HIV treatment failure [ 144 ••]. This evidence has possible detrimental results for HIV-associated PE women as both conditions exhibit a decrease in miR-126.…”
Section: Micrornas In Angiotensin-converting Enzyme 2 Receptorsmentioning
confidence: 99%
“…Additionally, MiR-16-5p has been linked with the pathogenesis of several infectious diseases such as HIV-1 infection and malaria [ 105 , 106 , 107 ]. It is worth mentioning that miR-16-5p as a plasma diagnostic biomarker is able to distinguish severe and mild viral infections [ 108 ] and early HIV-1 infection from healthy individuals [ 106 , 109 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, MiR-16-5p has been linked with the pathogenesis of several infectious diseases such as HIV-1 infection and malaria [105107]. It is worth mentioning that miR-16-5p as a plasma diagnostic biomarker is able to distinguish severe and mild viral infections [108] and early HIV-1 infection from healthy individuals [106,109].…”
Section: Discussionmentioning
confidence: 99%